2015
DOI: 10.1002/icd.1951
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maltreatment Type on Adolescent Executive Functioning and Inner Speech

Abstract: There are indications that different types of maltreatment can lead to different cognitive and behavioural outcomes. This study investigated whether maltreatment type was related to executive functioning (EF) abilities and the use of inner speech. Forty maltreated adolescents and a comparison group of 40 nonmaltreated typically developing adolescents completed a battery of tasks designed to assess both their EF abilities and their vulnerability to disruptions to inner speech. They also completed an IQ test. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A total of 106 relevant articles were included; however, 15 articles were identified as redundant in the presence of more relevant articles that used the same sample. After the removal of redundancies, 91 articles were included in the meta-analysis. Eleven of these articles were identified from the references of included articles.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 106 relevant articles were included; however, 15 articles were identified as redundant in the presence of more relevant articles that used the same sample. After the removal of redundancies, 91 articles were included in the meta-analysis. Eleven of these articles were identified from the references of included articles.…”
Section: Resultsmentioning
confidence: 99%
“…Switching often had lower factor loadings than the other variables. In previous research involving comparisons of typically developing young people and those with disabilities, significant differences between these groups have been reported in Working Memory and Inhibition, but often there was no significant difference in Switching (e.g., Kirke‐Smith et al, 2016). Consequently, it may be that switching is less central to a range of EF abilities at this age or that our measures of switching are less appropriate (Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Another meta-analysis revealed that through affecting the left hemisphere of the brain, rTMS reduces medication-resistant auditory hallucinations and can be considered as an effective treatment option for afflicted patients (14). Similarly, several studies found the effectiveness of rTMS in significantly reducing auditory hallucinations and inner speech and improving working memory among patients with schizophrenia (9)(10)(11)(12)(13)(14)(15). The aim of this study was to evaluate the effects of highfrequency rTMS on auditory hallucinations and working memory among patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, a study reported the effectiveness of rTMS in significantly improving working memory and alleviating mood symptoms among patients with bipolar disorder (13). Another meta-analysis revealed that through affecting the left hemisphere of the brain, rTMS reduces medication-resistant auditory hallucinations and can be considered as an effective treatment option for afflicted patients (14). Similarly, several studies found the effectiveness of rTMS in significantly reducing auditory hallucinations and inner speech and improving working memory among patients with schizophrenia (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%